Heterogeneous expression of GABA receptor‐like subunits LCCH3 and GRD reveals functional diversity of GABA receptors in the honeybee Apis mellifera. (29th June 2020) - Henry, Christopher; Cens, Thierry; Charnet, Pierre; Cohen‐Solal, Catherine; Collet, Claude; van‐Dijk, Juliette; Guiramand, Janique; de Jésus‐Ferreira, Marie‐céleste; Menard, Claudine; Mokrane, Nawfel; Roussel, Julien; Thibault, Jean‐Baptiste; et al.
Abstract : Background and Purpose: Despite a growing awareness, annual losses of honeybee colonies worldwide continue to reach threatening levels for food safety and global biodiversity. Among the biotic and abiotic stresses probably responsible for these losses, pesticides, including those targeting ionotropic GABA receptors, are one of the major drivers. Most insect genomes include the ionotropic GABA receptor subunit gene, Rdl, and two GABA‐like receptor subunit genes, Lcch3 and Grd. Most studies have focused on Rdl which forms homomeric GABA‐gated chloride channels, and a complete analysis of all possible molecular combinations of GABA receptors is still lacking. Experimental Approach: We cloned the Rdl, Grd, and Lcch3 genes of Apis mellifera and systematically characterized the resulting GABA receptors expressed in Xenopus oocytes, using electrophysiological assays, fluorescence microscopy and co‐immunoprecipitation techniques. Key Results: The cloned subunits interacted with each other, forming GABA‐gated heteromeric channels with particular properties. Strikingly, these heteromers were always more sensitive than Am RDL homomer to all the pharmacological agents tested. In particular, when expressed together, Grd and Lcch3 form a non‐selective cationic channel that opens at low concentrations of GABA and with sensitivity to insecticides similar to that of homomeric Rdl channels. Conclusion and Implications: For off‐target species like the honeybee, chronic sublethal exposure to insecticides constitutes a major threat. At these concentration ranges, homomeric RDL receptors may not be the most pertinent target to study and other ionotropic GABA receptor subtypes should be considered in order to understand more fully the molecular mechanisms of sublethal toxicity to insecticides.